Sport activity in childhood: Early specialisation and diversification - Ford, P. R.; Williams, A. M. (Routledge handbook of talent identification and development in sport, 2017)
Sport activity in childhood takes place in formal and informal settings. Formal settings involve adults planning, organizing and leading activity for children, such as in coaching or physical education sessions and in competitions. Informal settings involve children leading the sport activities themselves without adult intervention, such as in playgrounds, parks, streets, gardens, car parks, homes, and beaches (Ford, 2016). In some sports in certain countries, children who are considered proficient or with potential are identified to engage in formal, competitive and systematic talent development programmes. In these programmes, children often specialize solely in the sport which has become known as early specialization (for a review, see Malina, 2010). Early specialization is defined as starting in the primary sport during childhood (5 to 12 years of age), starting in a talent development programme in childhood, and during that period engaging in one sport only, or at least primarily (Baker, Cobley, & Fraser-Thomas, 2009). Moreover, early specialization involves engaging in a relatively high volume and intensity of training in that sport, as well as in competition in that sport through tournaments, matches and/or leagues (Baker et al., 2009).